2019
DOI: 10.3390/app9122571
|View full text |Cite
|
Sign up to set email alerts
|

Review of Experimental Research on Supercritical and Transcritical Thermodynamic Cycles Designed for Heat Recovery Application

Abstract: Supercritical operation is considered a main technique to achieve higher cycle efficiency in various thermodynamic systems. The present paper is a review of experimental investigations on supercritical operation considering both heat-to-upgraded heat and heat-to-power systems. Experimental works are reported and subsequently analyzed. Main findings can be summarized as: steam Rankine cycles does not show much studies in the literature, transcritical organic Rankine cycles are intensely investigated and few pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 102 publications
(141 reference statements)
0
28
0
Order By: Relevance
“…Specifically, several factors affect the performance of ORC units: the thermal level of the external source, the working fluid, as well as the type of expander and operating conditions; therefore, the system architecture can vary significantly with the specific application and a standard setup is not completely established [11,32]. Moreover, the electric power of current geothermal systems is usually larger than 200 kW el with values also higher than 50 MW el [14,15,33,34]. On the other hand, few examples on small-scale ORCs are present, owing to higher specific costs and lower electric production [16,35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, several factors affect the performance of ORC units: the thermal level of the external source, the working fluid, as well as the type of expander and operating conditions; therefore, the system architecture can vary significantly with the specific application and a standard setup is not completely established [11,32]. Moreover, the electric power of current geothermal systems is usually larger than 200 kW el with values also higher than 50 MW el [14,15,33,34]. On the other hand, few examples on small-scale ORCs are present, owing to higher specific costs and lower electric production [16,35].…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of this work consists in the adoption of a transcritical ORC configuration with superheated conditions at the expander inlet. Transcritical systems show, in fact, higher performance compared to subcritical configurations [33,58] and provide a more efficient thermal exchange between the geofluid and organic fluid and lower irreversibility and exergy destruction [59]. Another benefit is the component downsizing due to the higher density of fluid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these literature studies, the main objective is one of improving ORC performance is by the use of different working fluids, changing turbine inlet parameters, and using different ORC design configurations (simple, regenerative, dual loop, etc.) [18,19]. In spite of the various experimental and theoretical studies, it is still not possible to precisely predict how much energy might be recovered and ORC performance due to the presence of various heat sources and dynamic variation of the heat source parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that the dryers widely used in other industries are not suitable for green coke drying. Given the advantageous material flow and heat transfer of shaft facilities [28][29][30], this work aims at designing a novel efficient drying system with a shaft dryer that is suitable for green coke drying, with sound energy usage [31] and low environmental impact [32,33]. In addition, key characteristics of the green coke, including particle size distribution [34], initial moisture content, vertex angle, pressure drop scheme [35], and the discharge characteristics, are essential to determine the parameters of the designed dryer [36].…”
Section: Introductionmentioning
confidence: 99%